Customer relationship management approach for MyFamily system: a framework - Kamaruddin, Zaleha; Othman, Roslina; Noordin, Mohamad Fauzan; Ismail , Amelia Ritahani; Zakaria, Noor Azura (IDOSI Publications, 2013)
CRM is an approach that is widely utilized by companies to increase the customer values and normally, it is adopted by business-oriented companies. There are various studies on the CRM which focused on developing customer-centric systems and strategies. Besides the business-oriented system, there is a need to develop a social-oriented system which can expand the customer relationship between the customer, experts and organization. Thus, in this paper, we describe the framework of the MyFamily system which is a socialoriented system with the aim to strengthen the family relationship. The system offers specific information and experts’ consultation for users as options to solve their family problems or issues. Besides the content being complemented with some personal touch, the system will also be integrated with approaches in knowledge management, information retrieval, ontology, taxonomy and visualization in order to enhance the delivery of experts’ consultation. This will certainly provide a new direction of the CRM approach that emphasizes on the social-oriented system.